Pembentukan Akhlakul Karimah Siswa melalui Pembiasaan Shalat Dhuha di MAN 2 Bekasi - Muammar Alwi, Muhammad; Latipah, Siti Latipah; Maulidina, Ana (Universitas Majalengka, 2024)
This study aims to identify the impact of the habit of dhuha prayer on the formation of students' noble morals. With the existence of dhuha prayer in the school environment, it is hoped that it can provide encouragement/motivation to improve education in Indonesia by instilling and accustoming students to practice good morals in an orderly and responsible manner and to cleanse qalbu from impurities of lust and anger so that the heart becomes clean. The research method used in this study is a type of qualitative research. The type of approach used in this study is the type of phenomenology, which is research that reveals events with actual events. The research location at MAN 2 Bekasi is located on Jl. Amaraden No.2, Cibening, Setu District, Bekasi Regency, West Java. The results of this study reveal that the benefits of dhuha prayer for MAN 2 Bekasi students are that students feel comfortable, calm, and have a clear mind. As well as the benefits of dhuha prayer in the formation of moral character of MAN 2 Bekasi students are that students have better behavior, such as discipline in carrying out dhuha prayers and carrying out daily activities at MAN 2 Bekasi.